Management Analysis of Pandemic Covid-19 in Kepung, Kediri Districts - Giartiningsih Giartiningsih (Journal for Quality in Public Health, 2021)
Pandemic is a recurring event that causes a global recession and threatens human security. The Covid-19 pandemic in Indonesia is predicted to have very high morbidity and mortality rate. The strategy has been implemented but the case is still high, so it needs to be evaluated of the management factor from task force and community health center. The research method used is descriptive qualitative, with purposive sampling and indeep interview of 16 main informants and 2 triangulation informants. The research results from the input aspect of man and money are sufficient, lack of material becouse of regulations, budgets, stock and information that cause negative stigma and inadequate movement of task force and inadequate mentoring methods due to weak coordination. The planning aspects consider community input (batoom up), fulfillment of guidelines and instructions from the health office or district task force (top down) with a system of changes to the Financial Budget. The conclusion is that the preventive and promotive roles of community health center management and task forces are not maximal in efforts to deal with a pandemic becouse of limited inputs and constraints in organization and implementation.